Hospitalization as a chance to update the basic vaccination calendar: an experience carried out at the university hospital in São Luís – MA - Ana Louise de Araújo Carvalho; Danielle Luce Almeida Oliveira; Waldeise Pereira; Francisca Georgina Macedo de Sousa (Rev Rene)
To consider hospitalization as a chance to update the basic calendar of vaccination was our challenge when we performed practical activities for Pediatric Nursing. From July 11 to 18, 2003 there were 57 children in the hospital and the instrument for data collection was the analysis of the vaccination calendar. Nursing visit was the moment for the evaluation of the vaccine situation. Of those children, 36.8% were younger than 1 year old and 54.3% were from the countryside of the state; 47.4% presented a delayed or incomplete vaccine project whereas 21.0% presented a complete and updated project. Despite being sick, 73.1% of the children were vaccinated whereas 26.9% were not vaccinated for presenting relative and absolute contraindications. Hospitalization is, therefore, an excellent strategy to update a vaccine project and to increase vaccine covering.